Miocene to Early Pleistocene Depositional History and Tectonic Evolution of the Issyk‐Kul Basin, Central Tian Shan. (22nd April 2021) - Roud, Sophie C.; Wack, Michael R.; Gilder, Stuart A.; Kudriavtseva, Anna; Sobel, Edward R.
Abstract: The Issyk‐Kul Basin (Kyrgyzstan), situated in the central Tian Shan Mountains, hosts the largest and deepest mountain lake in Central Asia. Erosion of the surrounding Terskey and Kungey ranges led to the accumulation of up to 4 km of sediment in the adjacent depression. Creation of the basin from regional shortening and uplift likely initiated around the Oligocene‐Miocene, yet precise age control is sparse. To better understand the timing of these processes, we obtained magnetostratigraphic age constraints on fossil‐poor, fluvio‐lacustrine sediments exposed south of Lake Issyk‐Kul, that agree well with previous age constraints of the equivalent strata outside the Issyk‐Kul Basin. Two 500–650 m thick sections comprised mainly of Chu Group sediments were dated at 6.3–2.8 Ma and 7.0–2.4 Ma (late Miocene to early Pleistocene). Together with reinterpreted magnetostratigraphic constraints from underlying strata, we find that syn‐tectonic deposition commenced at ∼22 Ma with average sedimentation rates <10 cm/ka. Sedimentation rates increased to 10–30 cm/ka at 7 Ma, concurrent with accelerated uplift in the Terskey Range to the south. A deformation event in one section (Kaji‐Say) between 5 and 3 Ma together with concurrent shifts of depositional centers throughout the basin signal the onset of substantial uplift of the Kungey Range to the north at ∼5 Ma. This uplift and deformation transformed the Issyk‐Kul area into a closed basin that facilitated the formation of a deep lake. Lacustrine facies deposited around 3 Ma mark the existence of Lake Issyk‐Kul by that time. Plain Language Summary: In this study, we investigated how and when the sedimentary basin that contains the deepest mountain lake in central Asia (Lake Issyk‐Kul) formed. The sediments originated from the surrounding Tian Shan Mountains that were exhumed by tectonic forces related to the collision between the Indian and Eurasian plates. Sediments accumulated in the Issyk‐Kul Basin as the nearby mountains eroded. By determining detailed records of sedimentation ages and deposition rates, we found that the oldest sediments stemming from mountain building are 22 Myr old, suggesting that uplift initiated then. Around 7 Ma, sedimentation rates increased 2–3 times, thereby signifying a time of accelerated uplift and erosion. After 5 Ma, sedimentary layers south of the lake were strongly deformed, while sedimentation patterns shifted throughout the basin, likely caused by the uplift of mountains farther north. This transformed the Issyk‐Kul area into a closed basin, thereby facilitating the formation of a deep lake. Carbonate‐rich facies became widespread around 3 Ma, further confirming the existence of Lake Issyk‐Kul. Key Points: Mountain building and syn‐tectonic deposition in the Issyk‐Kul Basin began at ∼22 Ma and accelerated at ∼7 Ma Deformation propagated northward at ∼5 Ma, initiating the closure of the basin and facilitating the formation of a deep Lake Issyk‐Kul Comparable depositional ages of equivalent strata throughout the central Tian Shan suggest regionally synchronized geologic processes